Corporate governance mechanisms, innovation, and strategic management accounting disclosure: the moderating role of board gender diversity - James, Bernadette Josephine; Joseph, Corina; Said, Roshima (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2025)
This paper aims to examine the moderating effect of the board gender diversity in explaining the relationship between the corporate governance mechanisms, innovation, and the extent of strategic management accounting disclosures in the Malaysian public listed companies’ annual reports from the perspective of the research-based view theory. The content analysis technique was employed to collect data (dependent, independent, moderating, and control variables) from 180 public listed companies for the year 2021. The extent of strategic management accounting disclosure in annual reports of the Malaysian public listed companies revealed a ‘marginally satisfactory’ level at 46%. The hierarchical regression analysis revealed that board size, board independence, foreign ownership, and innovation significantly influenced the extent of strategic management accounting disclosure in Malaysia. The study found that board gender diversity moderated the relationship between board size and SMAD in 2021. The resource-based view theory has been successfully used in this study in conceptualizing the board size, board independence, foreign ownership, and innovation as companies’ unique resources that are valuable, rare, inimitable, and non-substitutable. This study contributes to the improvement in strategic management accounting disclosure amongst the publicly listed companies in Malaysia for business sustainability. In response to MCCG 2021 calls for informative and valuable disclosures, disclosing strategic management accounting information helps to instil trust and confidence in the various stakeholders that companies can sustain its business despite the impact of any future crises.